2018
DOI: 10.3389/fphar.2018.01291
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting Anion Exchange of Osteoclast, a New Strategy for Preventing Wear Particles Induced- Osteolysis

Abstract: Joint replacement is essential for the treatment of serious joint disease. However, prosthetic failure remains an important clinical issue, with periprosthesis osteolysis (PO), caused by osteoclastic bone resorption induced by wear particles, being the leading cause of failure. Nuclear factor of activated T cells c1 (NFATc1) appears to play an important role in wear particle-induced osteoclastogenesis, with bicarbonate/chloride exchanger, solute carrier family 4, anion exchanger, member 2, (SLC4A2) being upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…ZYX can repair the vascular endothelial injury by regulating endothelial cell exocytosis to reorganize the local actin network ( 65 ). Previous studies have shown that SLC4A2-mediated osteoclast anion exchange affects bone resorption by regulating pHi ( 66 , 67 ). PPP1R15A promotes apoptosis, alleviating stress-induced osteoblast damage ( 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…ZYX can repair the vascular endothelial injury by regulating endothelial cell exocytosis to reorganize the local actin network ( 65 ). Previous studies have shown that SLC4A2-mediated osteoclast anion exchange affects bone resorption by regulating pHi ( 66 , 67 ). PPP1R15A promotes apoptosis, alleviating stress-induced osteoblast damage ( 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…As SLC4A2 plays a role in forming the actin rings of osteoclasts, it is considered a pathogenic gene to treat periprosthesis osteolysis. DIDS, which blocks SLC4A2 expression, has a positive effect on the reduction of the region that resorbs the bone, providing plausible evidence for its role in the therapeutic strategy of osteoclastic-associated osteolytic diseases [122].…”
Section: Slc4a2mentioning
confidence: 98%
“…A future challenge will be deciphering the exact contribution of each SLC4A2 variant in OCs as well as exploiting this transporter family for therapeutic targeting. A recent study demonstrating that the anion exchange inhibitor 4, 4 -diisothiocyano-2,2 -stilbenedisulfonic acid (DIDS) is capable of suppressing OC activity in a mouse model of wear-particle-induced osteolysis (Wu et al, 2018) lends 'proof of principal' toward this.…”
Section: Slc4a2mentioning
confidence: 99%